Cerai Gugat Pasangan Pernikahan Dini Atas Penelantaran Prespektif Gender - Latassaqia, Rita (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the phenomenon of contested divorce raised by early marriage couples in Temanggung Regency, with a focus on household neglect from a gender perspective. Data shows that the number of divorce suits filed by wives reaches 90% due to neglect committed by the husband, reflecting deep gender injustice in the social structure. This research used qualitative methods with in-depth interviews with 10 interviewees, including plaintiffs and court officials, as well as analysis of relevant legal documents. The urgency of this research lies in the high rates of early marriage and divorce in Temanggung, which contribute to an increase in domestic violence cases. Data from the Central Bureau of Statistics shows that early marriages in Temanggung increased by 18.3% in 2020, with the divorce rate continuing to rise. This study highlights its novelty by comparing the results with previous studies that focus more on the causal factors of early marriage, while this study emphasizes the impact of domestic abuse as a form of domestic violence that is often overlooked. The results show that domestic abuse not only impacts the psychological and economic well-being of the wife, but also has implications for the well-being of the children. This abuse often goes unnoticed by the victim, resulting in a continuous cycle of violence. The conclusions of this study emphasize the need for more effective pre-marital education programs and policies that support gender equality, including the strengthening of regulations that protect the rights of women and children. Concrete policy implications include mediating development programs at the community level and increasing access to education for women to reduce early marriage and divorce rates in the Temanggung District.Penelitian ini bertujuan untuk menganalisis fenomena cerai gugat yang diangkat oleh pasangan pernikahan dini di Kabupaten Temanggung, dengan fokus pada penelantaran rumah tangga dari perspektif gender. Data menunjukkan bahwa jumlah cerai gugat yang diajukan oleh istri mencapai 90% akibat penelantaran yang dilakukan oleh suami, mencerminkan ketidakadilan gender yang mendalam dalam struktur sosial.  Urgensi penelitian ini terletak pada tingginya angka pernikahan dini dan cerai gugat di Temanggung, yang berkontribusi pada peningkatan kasus kekerasan dalam rumah tangga (KDRT). Penelitian ini merupakan penelitian hukum empiris. Penelitian ini menyoroti kebaruan dengan membandingkan hasil dengan penelitian sebelumnya yang lebih fokus pada faktor penyebab pernikahan dini, sementara penelitian ini menekan dampak penentaran rumah tangga sebagai bentuk KDRT yang sering diabaikan. Hasil penelitian menunjukkan bahwa penelataran rumah tangga tidak hanya berdampak pada kesejahteraan psikologis dan ekonomi istri, tetapi juga berimplikasi pada kesejahteraan anak. Penelitian ini sering kali tidak disadari oleh korban, yang mengakibatkan siklus kekerasan yang berkelanjutan. Kesimpulan dari penelitian ini menekankan perlunya program pendidikan pra-nikah yang lebih efektif dan kebijakan yang mendukung kesetaraan gender, termasuk penguatan regulasi yang melindungi hak-hak perempuan dan anak. Implikasi kebijakan yang secara konkret mencakup mediasi program pengembangan di tingkat komunitas dan peningkatan akses pendidikan bagi perempuan untuk mengurangi angka pernikahan dini dan cerai gugat di Kabupaten Temanggung.
Keywords: Diforce Lawsuit; Neglect